Psychometric properties of the Italian version of the Forgotten Joint Score in patients with total hip arthroplasty. Issue 4 (6th October 2022) - Angilecchia, Domenico; Stano, Flavia; Signorelli, Maria; Giovannico, Giuseppe; Pournajaf, Sanaz; Pellicciari, Leonardo
Abstract : Total hip arthroplasty (THA) surgeries are increasing; to assess quality of life after THA, an instrument that considers patient's perspective on surgical outcomes is necessary. The objective of this study is to assess the psychometric properties of the Italian version of the Forgotten Joint Score (FJS-I) in patients with THA. The FJS-I was administered to 111 patients with THA, as well as the Western Ontario and McMaster Universities (WOMAC), Numerical Pain Rating Scale (NPRS), and the EuroQol 5D-5L (EQ-5D-5L). Structural validity [confirmatory factor analysis (CFA)], internal consistency (Cronbach's alpha), test–retest reliability [intraclass correlation coefficient (ICC2, 1 )], measurement error [standard error of the measurement (SEM)], and construct validity (hypothesis testing with correlation of the WOMAC, NPRS, and EQ-5D-5L) were assessed. In addition, the minimal detectable change (MDC) was computed. The result of CFA confirmed the one-factor structure. Internal consistency was supported (α = 0.944). A high test–retest reliability (ICC = 0.958; 95% confidence interval, 0.914–0.980) was found with an SEM and an MDC of 5.3 and 16.6 points, respectively. The a-priori hypotheses were fully met, determining the construct validity to be satisfactory. Psychometric properties of the FJS-I were confirmed, and it can be used for single-person assessment. Further research is suggested to refine its structural validity.